A systematic review of measures of self-reported adherence to unsupervised home-based rehabilitation exercise programmes, and their psychometric properties. Issue 6 (27th June 2014) - Bollen, Jessica C; Dean, Sarah G; Siegert, Richard J; Howe, Tracey E; Goodwin, Victoria A
Abstract : Background: Adherence is an important factor contributing to the effectiveness of exercise-based rehabilitation. However, there appears to be a lack of reliable, validated measures to assess self-reported adherence to prescribed but unsupervised home-based rehabilitation exercises. Objectives: A systematic review was conducted to establish what measures were available and to evaluate their psychometric properties. Data sources: MEDLINE, EMBASE, PsycINFO CINAHL (June 2013) and the Cochrane library were searched (September 2013). Reference lists from articles meeting the inclusion criteria were checked to ensure all relevant papers were included. Study selection: To be included articles had to be available in English; use a self-report measure of adherence in relation to a prescribed but unsupervised home-based exercise or physical rehabilitation programme; involve participants over the age of 18. All health conditions and clinical populations were included. Data extraction: Descriptive data reported were collated on a data extraction sheet. The measures were evaluated in terms of eight psychometric quality criteria. Results: 58 studies were included, reporting 61 different measures including 29 questionnaires, 29 logs, two visual analogue scales and one tally counter. Only two measures scored positively for one psychometric property (content validity). The majority of measures had no reported validity or reliability testing. Conclusions: The results expose a gap in the literature for well-developed measures that capture self-reported adherence to prescribed but unsupervised home-based rehabilitation exercises.